Ang pagbubuntis ni Ligaya - Lugtu, Jean Louise Bustos; Dalena, Sari Raissa Lluch (Quezon City College of Mass Communication, University of the Philippines, 2023)
Ang Pagbuhuntis ni Ligaya follows a 68-year-old matandang dalaga (old maid) who experiences the symptoms of pregnancy when her 19-year-old niece unexpectedly pays a visit to her home. As they spend time together talking and reflecting on their experiences of singleness and womanhood, the two women are forced to deal with the cards that life has handed them. In the end, one of them is left to make a choice for her future.

The framework used in constructing the narrative was Erikson's Stages of Psychosocial Development to weave together the story of two women in different life stages against the backdrop of a patriarchal system that oppresses them. Through a feminist lens, the film explores the sensibilities of single elderly women who are often at the receiving end of negative stereotypes in Filipino culture. The film attempts to show that while there exists a fulfillment of life within marriage and motherhood, there also exists fulfillment outside of it.
Vita.
Thesis
Includes bibliographical references (page 109) and appendices (pages 110-153).
Keywords: Single women -- Philippines; Teenage pregnancy -- Philippines; Abortion -- Philippines